2021
DOI: 10.7150/thno.61480
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota dysbiosis and gastric tumorigenesis

Abstract: The gastrointestinal tract contains a vast and diverse microbial reservoir composed of bacteria, fungi, and viruses that contribute positively to human health. There is growing evidence that perturbation of the normal microbiota can promote a variety of human disease states that include tumorigenesis. Whether the fungal component of the gut microbiota (i.e., the mycobiota) can influence tumor development has not been investigated in detail. In the recent issue of the Theranostics , Zhong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…As shown in Table 3 [31]. Together with our findings, these recent advancements not only support that certain commensal fungi might be related to gastrointestinal cancers, [32] but also highlight the feasibility of mycobiota-driven approaches to identify patients at risk of gastrointestinal disease and cancers. Studies using animal models found a ~ 3000-fold fungal increase in PDAC [3].…”
Section: Logistic Regression For Mycobiota Profilesupporting
confidence: 80%
“…As shown in Table 3 [31]. Together with our findings, these recent advancements not only support that certain commensal fungi might be related to gastrointestinal cancers, [32] but also highlight the feasibility of mycobiota-driven approaches to identify patients at risk of gastrointestinal disease and cancers. Studies using animal models found a ~ 3000-fold fungal increase in PDAC [3].…”
Section: Logistic Regression For Mycobiota Profilesupporting
confidence: 80%
“…Notably, the existence of a significant correlation between gastric dysbiosis and aforementioned pathologies was observed, highlighting the importance of perturbations in the gastric microbiome in the etiopathology of gastric diseases [ 24 , 27 , 28 , 53 ]. Moreover, an association between dysbiosis of the fungal gastric community and the development of gastritis, ulcers and gastric cancer has been also proven in several studies, indicating the significance of microbiota dysbiosis [ 47 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research on the role of fungal and viral microbiota in tumors is relatively limited compared to bacteria ( Papon et al, 2021 ). However, studies have identified a significant elevation of Candida albicans in GC patients ( Zhong et al, 2021 ).…”
Section: Gastric Microbial Dysbiosis In Correa’s Cascadementioning
confidence: 99%